2006
DOI: 10.1103/physrevb.73.094510
|View full text |Cite
|
Sign up to set email alerts
|

Two-gap superconductivity inZrB12: Temperature dependence of critical magnetic fields in single crystals

Abstract: We report the measurements of the temperature dependence of the resistivity, ρ(T), magnetic penetration depth, λ(T) the lower, H c1 (T), and upper, H c2 (T), critical magnetic fields, for single crystals of dodecaboride ZrB 12 , diboride ZrB 2 and thin films of diboride MgB 2 . We observe a number of deviations from conventional behavior in these materials. Although ZrB 12 behaves like a simple metal in the normal state, the resistive Debye temperature, 300 K, is three times smaller relative to that (800-1200 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
59
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 54 publications
7
59
1
1
Order By: Relevance
“…In fact, single crystals of this compound (ZrB 2 ) are not superconducting. 14 The Zr-B phase diagram suggests that contamination with ZrB 12 , a known superconductor with critical temperature 5.94 K. 15 ZrB 2 , also was studied to high pressure (50 GPa) and no superconductivity was observed. 16 In this work we present a systematic study of substitution of Zr for V in Zr 1−x V x B 2 (0 x 1.0) and find that superconductivity emerge in the nonsuperconductor ZrB 2 matrix for a small content of V, an example where an extremely stressed lattice of the AlB 2 prototype yields superconductivity while the matrix compound is nonsuperconducting.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, single crystals of this compound (ZrB 2 ) are not superconducting. 14 The Zr-B phase diagram suggests that contamination with ZrB 12 , a known superconductor with critical temperature 5.94 K. 15 ZrB 2 , also was studied to high pressure (50 GPa) and no superconductivity was observed. 16 In this work we present a systematic study of substitution of Zr for V in Zr 1−x V x B 2 (0 x 1.0) and find that superconductivity emerge in the nonsuperconductor ZrB 2 matrix for a small content of V, an example where an extremely stressed lattice of the AlB 2 prototype yields superconductivity while the matrix compound is nonsuperconducting.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the experimental Fermi surface in this cluster compound is critical for understanding two-gap model suggested in Ref. 6. Until now there have been no direct experimental probes of the FS structure of ZrB 12 .…”
Section: Introductionmentioning
confidence: 98%
“…Matthias et al [1] suggested that the superconductivity in YB 6 and ZrB 12 was due to the effect of a cluster of light boron atoms. Much smaller isotope effect on T c for boron in comparison with Zr isotopic substitution suggests that the boron in ZrB 12 serves as inert background for the Zr driven superconductivity [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations